Post-COVID-19 syndrome among symptomatic COVID-19 patients: A prospective cohort study in a tertiary care center of Bangladesh - Mahmud, Reaz; Rahman, Md. Mujibur; Rassel, Mohammad Aftab; Monayem, Farhana Binte; Sayeed, S. K. Jakaria Been; Islam, Md. Shahidul; Islam, Mohammed Monirul (PloS one, 2021)
Post-coronavirus disease (COVID-19) syndrome includes persistence of symptoms beyond viral clearance and fresh development of symptoms or exaggeration of chronic diseases within a month after initial clinical and virological cure of the disease with a viral etiology. We aimed to determine the incidence, association, and risk factors associated with development of the post-COVID-19 syndrome. We conducted a prospective cohort study at Dhaka Medical College Hospital between June 01, 2020 and August 10, 2020. All the enrolled patients were followed up for a month after clinical improvement, which was defined according the World Health Organization and Bangladesh guidelines as normal body temperature for successive 3 days, significant improvement in respiratory symptoms (respiratory rate <25/breath/minute with no dyspnea), and oxygen saturation >93% without assisted oxygen inhalation. Among the 400 recruited patients, 355 patients were analyzed. In total, 46% patients developed post-COVID-19 symptoms, with post-viral fatigue being the most prevalent symptom in 70% cases. The post-COVID-19 syndrome was associated with female gender (relative risk [RR]: 1.2, 95% confidence interval [CI]: 1.02-1.48, p = 0.03), those who required a prolonged time for clinical improvement (p<0.001), and those showing COVID-19 positivity after 14 days (RR: 1.09, 95% CI: 1.00-1.19, p<0.001) of initial positivity. Patients with severe COVID-19 at presentation developed post-COVID-19 syndrome (p = 0.02). Patients with fever (RR: 1.5, 95% CI: 1.05-2.27, p = 0.03), cough (RR: 1.36, 95% CI: 1.02-1.81, p = 0.04), respiratory distress (RR: 1.3, 95% CI: 1.4-1.56, p = 0.001), and lethargy (RR: 1.2, 95% CI: 1.06-1.35, p = 0.003) as the presenting features were associated with the development of the more susceptible to develop post COVID-19 syndrome than the others. Logistic regression analysis revealed female sex, respiratory distress, lethargy, and long duration of the disease as risk factors. Female sex, respiratory distress, lethargy, and long disease duration are critical risk factors for the development of post-COVID-19 syndrome.